A matter of timing: Analyzing and adjusting library hours to suit students. Issue 2 (3rd April 2021) - Migdalski, Alyssa; Moreau, Emrys
Abstract: The objective of this article is to describe an operating hours study conducted via survey at the Schusterman Library, a small academic library located at a branch campus of the University of Oklahoma. Survey responses indicated that although a small majority of library users were satisfied with the hours, there was also a strong desire for increased library access on weekends. As a result of this survey, Schusterman Library administration decided to reallocate five hours from weekday evenings to Saturday mornings. This change in operating hours was evaluated with a follow up survey and an analysis of gate count data.